A pena e sua execução em face dos princípios constitucionais penais e processuais penais - Zanoni, Luciana Ortiz Tavares Costa (2002)
This is about a study of the punishment and its execution in view of the constitutional and criminal procedural principles. The study approaches the historical evolution of the confinement, which is inseparable from the maio theories and movements of the criminal politics related to the punishment. It concludes that the punishment must have as a purpose the prevention that is limiting, general and positive, as well as the prevention that is special. The punishment segregates the convict, although taking into consideration the view of the guarantee. Therefore, the alternative punishments are considered of great importance. Some reading of the punishment in the Democratic State of Law is dane, pointing out the constitutional and criminal principles related to the punishment and are following analyzed considering the alternative punishments. With no intention to exhaust the theme, the significant aspects of it were approached. Demonstrating that alternative punishments, which possibility of application was significantly widened by the Law n. 9.714/98, must have a constitutional reading , without it there is a failure risk as happened with the confinement. It is emphasized the need of a growing jurisdictional prócess concerning the criminal execution, as a way of assuring the fulfillment of the exact terms of the execution of the criminal condenation, where the constitutional guarantees of the convict are implicit. The criminal procedural principles related to the execution of the punishment are considered, taking into account some significant constitutional issues. At last, the responsibility of the community to the execution of the punishment is pointed out, since the return of the ex-convict to the society is a social problem. We concluded that only respecting the postulates of The Democratic State of Law will make of the alternative punishments an effective instrument to humanize the penal system